Is higher insertional torque of interference screw associated with higher pull-out strength of reconstructed ACL graft? - Mohamed Faizal Bin Mohamed Raffi (Nanyang Technological University, 2022)
The Anterior Cruciate Ligament (ACL) is one of the 4 main ligaments on the knee. They are the primary ligaments which provide stability and rotational movement of the knee joint. Athletes are most prone to ACL related injuries due to vigorous movements such as quick changing of directions. While providing stability to the knee during sports activities, the ACL also helps centre the body weight through the knee joint. This helps in reducing wear and tear on the other parts of the joint [1]. When an ACL is fully ruptured, more often than not, a reconstruction surgery is required. This project is to test the strength of the ACL graft in relation to the insertional torque of the interference screw used in the ACL reconstruction. The hypothesis of the study is that the higher the insertional torque of the interference screw, the higher the pullout strength of the graft. Currently, there is no study to correlate the insertional torque of the interference screw with the pull-out strength of the reconstructed graft. Bovine tendons were used as ACL graft substitutes and artificial bone blocks were used to simulate the human bone. Bone blocks of 3 different densities (10, 20 and 30 pounds per cubic foot) were tested using Instron 5566 machine. The torque of the interference screw was measured using a digital torque wrench. Cyclic loading of maximum 200 N at 5 mm/s was carried out to mimic the daily use of the ligaments before the tendons were pulled to failure. Results showed that the pull-out force does increase as the insertional torque increases within the specific density. Higher density does not yield a higher pull-out force.